Construction of Validity and Reliability of The SBAR-Based Assessment Scale among Nurses - Blacius Dedi; Rita Dewi Sunarno; Aris Payung (JURNAL INFO KESEHATAN, 2025)
Situation, Background, Assessment, Recommendation (SBAR) is a communication tool used to convey information clearly and in a structured manner, especially in the context of health services. The implementation of this assesment scale consideration has not been carried out optimally for nurses in the hospital. This study aims to analyze the validity and reliability of the SBAR-based weighing evaluation instrument from primary nurses and associate nurses. Multivariate validity and reliability test using the Exploratory Factors Analysis (EFA) test. The results aim to validate the instrument content. The numbers in the table show the loading factor values for each statement item which have been sorted from the largest value to the smallest value for each component. Statement items are valid and have an important correlation in the handover implementation instrument if they have a factor loading value of <0.40. Of the 25 statement items, 8 items were invalid, namely item numbers 2,3,4,6,10,12,17,19 while the other 17 items were declared valid and formed 4 components (Component 1; Situation indicator, Component 2; Backgound indicator, Component 3; Assessment indicator, Component 4; Assesment) which were used as indicators for compiling the SBAR-based handover implementation instrument. CFA test results were the relative chi-square value (CMIN/df) shows a fairly good fit with a ratio <5, the comparative fit index (CFI) value indicates marginal fit because it is in the range 0.80<CFI <0.90, The root mean square error (RMSEA) value indicates a reasonable agreement with a value of <0.08, the goodness-of-fit (GoF) value indicates a good fit because it is >0.80. It can be interpreted that based on the results of the CFA analysis it has fulfilled the construct feasibility test so that in general it can be said that the handover evaluation instrument by primary nurses and associate nurses is fit to be used in measuring handover implementation.